SISTEM PENERANGAN SELASAR RUMAH SAKIT BERBANTUAN PENGINDRAAN INFRA MERAH BERBASIS ECOGREEN - Frisa Yugi Hermawan; Puji Rachmanto (Jurnal Ilmu dan Teknologi Kesehatan, 2017)
This intelligent system is made as the application of teaching materials in lighting system for Hospital hallway. Hospital as a public health facilities is commonly visited by people thus it must have a lighting system to make people feel save and comfort. The purpose of this research is to test the intelligent system modeling module by integrating series of parallelseries lamps and infrared sensors as a single moving object detector. The research employ series of activity from literature review process of various sources, designing the integrastion system, programing, component test, and testing the whole function of program and tool. The progran was conducted by arranging three groups of lights with different lit order, referring to four Infra Red sensors. Each light poweredfixed power valueusingnamely 25 Watt in parallel circuit and the power used changed into 10 Watt when in the series. The bounce state is found when the lamp circuit is connected to a voltage source. The results of this study indicate that the regulation of ligth power value by intelligent system, which is illuminated in parallel circuit is 25 Watt, can be decreased to 10 Watt in series circuit. Decrease of light power by 60% either per ligth or in group of ligth can be controlled by intelligent system without reducing the comfort of lighting the hallway.